Factors Indicating Stock Value in the Market for Alternative Investment (MAI): A Financial Indicator Perspective - Kumsin, Pattanapong; Robkob, Aukkarawit (MBA-KKU Journal, 2026)
This study investigates the financial determinants of stock value in the Market for Alternative Investment (MAI). The financial indicators examined in this study included return on assets, return on equity, quick ratio, debt-to-equity ratio, gross profit margin, accounts receivable turnover, and accounts payable turnover. Data were collected from companies listed on the MAI between 2019 and 2023, comprising 545 observations from 109 companies. The data were analyzed using multiple regression analysis. The results showed that return on assets and gross profit margin positively influenced stock value in the MAI. This indicates that changes in these indicators were associated with corresponding changes in stock prices. In contrast, return on equity and debt-to-equity ratios were found to negatively impact stock value. Higher levels of ROE and debt-to-equity ratio were associated with lower stock value, whereas lower levels were associated with higher stock value. Furthermore, the study found that companies listed on the MAI employed various financial indicators to reflect operational efficiency, financial position, and profitability. Companies with high ROA and gross profit margins demonstrated stronger operational performance and greater potential for value creation. Conversely, companies with high debt-to-equity ratios may face greater financial structure risk, which should be carefully considered when evaluating stock value.